Otimização da avaliação da matéria prima e comprimidos de atenolol: aplicação em produção, controle e registro de medicamento genérico - Prado, Anelise Weich do (2007)
The atenolol is a selective β-blocker that acts specially on β-one adrenergic receptors of the heart, used in the control of high blood pressure, pectoris angine, cardiac arrhythmias and the treatment of miocardic stroke. This paper aimed to optimize the described methodologies for drugs and tablets of atenolol. It proposes to develop and validate simple and more accessible tests to evaluate atenolol tablets and raw material. It also emphasizes the ideal characteristics for drugs in the pre-formulation and development of the pharmaceutical form. Methodologies were developed and validated by HPLC and UV spectrophotometric for the quantification of atenolol in tablets. Raw material characterization techniques were also applied for the classification of atenolol in the pre-formulation. A pharmaceutical equivalence test was performed and compared to the national market reference drug. The HPLC developed method presents advantages over the official methodology to establish an analysis without the use of ionic pareator heptane sulphonate, for being faster and more simple. Both quantitative development methods were linear, specific exact, precise, robust and equivalent between themselves. For the dissolution performed with atenolol pharmaceutical form, after the dissolution efficiency analysis no meaningful difference were observed between the obtained dissolution curves through developed methods and the pharmacopeial methodology. The atenolol raw material analysis permitted its characterization, assuring an adequate use in the pharmaceutical form manufacturing. The comparative analysis between the test drug and reference drug allowed to claim that the two formulations are similar and with the some in vitro performance, i.c., they are pharmaceutical equivalent. The described methods are useful in routine quality analysis control of atenolol. The comparative analysis between the proposed methods and official methodology demonstrated that there is no statistical meaningful differences characterizing their equivalence.